Foraminiferal Assemblages in the Cenomanian of the Buzet-Savudrija Area (Northwestern Istria, Croatia) - Ivo Velić (Geologia Croatica, 2010)
In the Cenomanian shallow-water carbonates of Northwestern Istria five biostratigraphic zones have been established: CEN-1 Ovalveolina maccagnoae and Sellialveolina viallii biozone in the early Lower Cenomanian; CEN-2 O. maccagnoae to Chrysalidina gradata interval zone in the late Lower Cenomanian; CEN-3 C. gradata biozone in the early Middle Cenomanian, locally subdivided into two subzones: CEN-3a C. gradata and orbitolinids (lower part) CEN-3b C. gradata without orbitolinids (upper part); CEN-4 C. gradata and Broeckina (P.) balcanica biozone in the late Middle Cenomanian, and CEN-5 C. gradata, B. (P.) balcanica and Vidalina radoicicae biozone in the Upper Cenomanian.